2016
DOI: 10.1159/000443864
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Alterations and Cardiovascular Outcomes of Cortisol Excess

Abstract: Cushing's syndrome (CS) is a severe chronic and systemic condition caused by endogenous or exogenous excess of glucocorticoids, associated with increased morbidity and mortality. Patients with active CS suffer from many metabolic alterations, including visceral obesity, systemic arterial hypertension, impairment of glucose metabolism and dyslipidemia. Additionally, in these patients several cardiovascular abnormalities, i.e. atherosclerosis, clotting disorders, left ventricular hypertrophy, concentric remodeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 73 publications
1
23
0
1
Order By: Relevance
“…As expected, ACS presented various cardiometabolic comorbidities, while both ACS and RCS presented, as compared to matched CTR, increased inflammatory parameters such as hs‐CRP, fibrinogen and an increased WHR . Interestingly, platelet number was increased only in ACS, while in RCS, platelet number correlated with sVCAM‐1.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…As expected, ACS presented various cardiometabolic comorbidities, while both ACS and RCS presented, as compared to matched CTR, increased inflammatory parameters such as hs‐CRP, fibrinogen and an increased WHR . Interestingly, platelet number was increased only in ACS, while in RCS, platelet number correlated with sVCAM‐1.…”
Section: Discussionsupporting
confidence: 63%
“…Several studies have demonstrated that remission of CS is associated with a significant improvement of metabolic parameters, although recovery is incomplete in the vast majority of cases, maintaining an increased cardiovascular risk . The mechanisms implicated are unclear and might involve vascular and circulatory factors due to the nonphysiological adrenal replacement therapy, another hormonal deficiency (growth or sexual hormones) and the persistence of increased visceral adipose tissue with deleterious cytokine secretion, maintaining an inflammatory and prothrombotic state and metabolic syndrome‐like features …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations